Heavy ion irradiation induced defects in Zircaloy-4 - TAV, CUMALİ; YAHŞİ, UĞUR (IOP PUBLISHING LTD, 2021)
Radiation damage induced in Zircaloy-4 by 20 MeV Au ions was investigated using Grazing x-ray diffraction (GIXRD), positron annihilation techniques, micro-and nano-hardness techniques. The irradiations were performed at room temperature in the fluence range 1 x 10(13)-5 x 10(14) ions cm(-2) corresponding to 0.07-3.63 displacements per atom (dpa). The grazing incidence angle x-ray diffraction (GIXRD) revealed the presence of the hydride precipitates in the analyzed zircaloy-4. According to our experimental data it is found that the amount of these precipitates decreases after irradiation as emphasized by GIXRD and Positron Annihilation Lifetime Spectroscopy (PALS) results. The same data revealed also a zircaloy-4 swelling above a certain dose. From the combination of domain size/microstrain with the micro- and nano-hardness results, we conclude that the Zircaloy hardening is mainly due to the dislocation formation indicating the effect of the microstructure on the mechanical properties. Moreover, from the dose dependence of irradiation hardening we conclude that the transition point from low-dose to high-dose regime is observed around 0.07 dpa.
Keywords: research reactor; Zircaloy-4; vacancies; dislocation loops; mechanical property; radiation damage; positron annihilation techniques